2015
DOI: 10.1038/ncomms9364
|View full text |Cite
|
Sign up to set email alerts
|

Bub1 autophosphorylation feeds back to regulate kinetochore docking and promote localized substrate phosphorylation

Abstract: During mitosis, Bub1 kinase phosphorylates histone H2A-T120 to promote centromere sister chromatid cohesion through recruitment of shugoshin (Sgo) proteins. The regulation and dynamics of H2A-T120 phosphorylation are poorly understood. Using quantitative phosphoproteomics we show that Bub1 is autophosphorylated at numerous sites. We confirm mitosis-specific autophosphorylation of a several residues and show that Bub1 activation is primed in interphase but fully achieved only in mitosis. Mutation of a single au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 70 publications
6
36
0
1
Order By: Relevance
“…For this purpose, we used a U2OS-Lac operator (LacO) cell line in which multiple copies of LacO repeats were stably integrated in a euchromatic region of chromosome 1p36 in U2OS cells (Janicki et al, 2004) ( Fig EV3H). As previously showed (Asghar et al, 2015), H2ApT120 was generated at the LacO transgene array targeted by Lac repressor (LacI)-fused Bub1 kinase domain (EGFP-LacI-Bub1-K), but not by the kinase-dead mutant EGFP-LacI-Bub1-K-D946N ( Fig 3D). Importantly, endogenous TOP2A was recruited to over 70% of the H2ApT120-positive transgene array targeted by EGFP-LacI-Bub1-K. By contrast, TOP2A was not recruited to the transgene array targeted by EGFP-LacI-Bub1-K-D946N.…”
Section: Bub1 Kinase Activity Is Necessary For Top2a Localization At supporting
confidence: 55%
See 1 more Smart Citation
“…For this purpose, we used a U2OS-Lac operator (LacO) cell line in which multiple copies of LacO repeats were stably integrated in a euchromatic region of chromosome 1p36 in U2OS cells (Janicki et al, 2004) ( Fig EV3H). As previously showed (Asghar et al, 2015), H2ApT120 was generated at the LacO transgene array targeted by Lac repressor (LacI)-fused Bub1 kinase domain (EGFP-LacI-Bub1-K), but not by the kinase-dead mutant EGFP-LacI-Bub1-K-D946N ( Fig 3D). Importantly, endogenous TOP2A was recruited to over 70% of the H2ApT120-positive transgene array targeted by EGFP-LacI-Bub1-K. By contrast, TOP2A was not recruited to the transgene array targeted by EGFP-LacI-Bub1-K-D946N.…”
Section: Bub1 Kinase Activity Is Necessary For Top2a Localization At supporting
confidence: 55%
“…(Tavormina et al, 2002). The Myc-LacI-Bub1 (WT or D946N) plasmids were kindly provided by Dr. Sabine Elowe (Université Laval, Québec, Canada) (Asghar et al, 2015). The VSV-Sgo1 plasmid was kindly provided by Dr. Susanne Lens (Oncode Institute, Utrecht, Netherlands) (Meppelink et al, 2015).…”
mentioning
confidence: 99%
“…It was shown that Bub1 phosphorylates the conserved histone H2A serine 121, which corresponds to H2A threonine 120 in humans. The histone H2A S121A mutant, in which all cellular H2A serine 121 is replaced by alanine, mimics the Bub1 kinase-dead mutant (Bub1-KD) in perturbing the centromeric localization of the Shugoshin protein, which is also associated with the pericentromeric chromosomal region and plays multiple roles in ensuring the accuracy of chromosome segregation during both mitosis and meiosis (Asghar et al, 2015;Baron et al, 2016;Lin, Jia, Tomchick, Luo, & Yu, 2014;Liu, Jia, & Yu, 2013;Liu et al, 2015;Marston, 2015). In addition to its role in histone H2A phosphorylation, it has also been reported that over-expression of Bub1 drives chromosomal instability through hyperactivation of Aurora B kinase (Ricke, Jeganathan, & van Deursen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fig 6B, C ). To evaluate BUB1 kinase activity, we used phosphospecific antibodies targeting the BUB1 autophosphorylation site T589 77 . Loss of the pseudokinase domain attenuated autophosphorylation of BUB1 at T589, in support of the notion that optimal BUB1 phosphorylation requires interaction with the BUBR1 pseudokinase domain (Fig 6D).…”
Section: Resultsmentioning
confidence: 99%
“…The following antibodies were used in this study at 1mg/mL, unless otherwise stated: anti-CENP-C (PD030, MBL International), mouse anti-CENP-E (1H12, Abcam), rabbit anti-CENP-E (C7488, Sigma), anti-H2A-pT120 (61195, Active Motif), anti-α-TUBULIN (DM1A, Santa Cruz), anti-MYC (9E10, Thermo Scientific), anti-HA (CloneHA7, H9658, Sigma), anti-FLAG (M2, F1804, Sigma), CREST anti-centromere serum (HCT-0100, Immunovision), and anti-ASTRIN (NB100-74638, Novus). The antibodies rabbit BUBR1-pS676 52 , mouse monoclonal BUBR1 52 , rabbit BUBR1-pS670 53 , anti-BUB1 53 , and rabbit BUB1-pT589 77 were previously described. Anti-KNL1 pS24 was a kind gift from Iain Cheeseman.…”
Section: Methodsmentioning
confidence: 99%